2016
DOI: 10.1080/15548627.2016.1240856
|View full text |Cite
|
Sign up to set email alerts
|

Human Atg8-cardiolipin interactions in mitophagy: Specific properties of LC3B, GABARAPL2 and GABARAP

Abstract: The phospholipid cardiolipin (CL) has been proposed to play a role in selective mitochondrial autophagy, or mitophagy. CL externalization to the outer mitochondrial membrane would act as a signal for the human Atg8 ortholog subfamily, MAP1LC3 (LC3). The latter would mediate both mitochondrial recognition and autophagosome formation, ultimately leading to removal of damaged mitochondria. We have applied quantitative biophysical techniques to the study of CL interaction with various Atg8 human orthologs, namely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 58 publications
5
55
0
Order By: Relevance
“…2A). Previous studies have demonstrated that LC3B translocated to mitochondria, resulting in the targeted removal of damaged mitochondria through the action of lysosomes [19]. Our results showed that the expression of LC3B was decreased in the cardiac mitochondria of db/db mice and neonatal rat cardiomyocytes treated with high glucose, oleate and palmitate ( Fig.…”
Section: Exogenous H2s Promoted Mitophagy In Cardiomyocytes Under Hypsupporting
confidence: 63%
“…2A). Previous studies have demonstrated that LC3B translocated to mitochondria, resulting in the targeted removal of damaged mitochondria through the action of lysosomes [19]. Our results showed that the expression of LC3B was decreased in the cardiac mitochondria of db/db mice and neonatal rat cardiomyocytes treated with high glucose, oleate and palmitate ( Fig.…”
Section: Exogenous H2s Promoted Mitophagy In Cardiomyocytes Under Hypsupporting
confidence: 63%
“…Previous studies from this laboratory have focused on the potential different roles of these two subfamilies, both in cargo recognition [22] and during autophagosome elongation [25]. Regarding cargo recognition, several aspects of the mitophagic mechanism initiated by CL externalization remain obscure.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding cargo recognition, several aspects of the mitophagic mechanism initiated by CL externalization remain obscure. Previous work from this laboratory [22] compared the behaviour of LC3B with that of GABARAP subfamily members. The study explored the differences in residues putatively involved in LC3B interaction with CL ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge Aβ42 binding to bilayers after separation of the free and lipid-bound forms of the peptide by density gradient centrifugation have rarely been performed. Vesicle-bound peptide floats in the density gradient whereas the non-bound protein/peptide, after aggregation, sediments [24,25]. The centrifugation method is quite unique in providing direct, quantitative equilibrium measurements of binding, in the absence of added probes or chemical modification of the ligand.…”
mentioning
confidence: 99%